Improving SMEs Marketing Performance through Market Orientation, Product Innovation, and Competitive Advantage in Bali-Indonesia - Pramuki, Ni Made Wisni Arie; Kusumawati, Ni Putu Ayu (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractDuring the COVID-19 pandemic, Small and Medium Enterprise (SMEs) as one of the elements driving economic growth had a tremendous impact on business productivity. However, this does not discourage SMI from showing excellent performance and being able to adapt to changes and business competitiveness. This study aims to analyze the role of market orientation as an antecedent in the relationship of product innovation to marketing performance through the competitive advantage of SMIs in Bali Province. This research method is quantitative with a survey approach. The sample size used was 125 samples of SMI managers. The analysis technique in this study uses a structural equation modeling (SEM) approach with the help of SmartPLS 3.2.9 software. The findings show that all the hypothesized variables can be verified. Keywords:Marketing Performance, Product Innovation, Market Orientation, Competitive Advantage